Analysis of Students’ Preferences and Needs for PJOK E-Module Development - Wibowo, Julian Tri; Kristina, Putri Cicilia; Handayani, Widya (PPSDP International Journal of Education, 2024)
The objective of this research was to evaluate students’ requirements for teaching materials in Physical Education, Sports, and Health (PJOK) with the goal of developing e-modules that effectively address these needs. The study utilized a descriptive exploratory approach, focusing on students from grades X and XI at SMA Negeri 15 Palembang. Participants were surveyed using a questionnaire distributed through Google Forms, which allowed students to articulate their preferences and needs regarding teaching materials. The research found that students exhibit a clear preference for digital teaching materials over printed ones. This preference is primarily driven by the practicality and convenience that digital resources offer, such as easy access, interactive features, and multimedia content. The questionnaire data revealed that students value the flexibility and enhanced engagement opportunities provided by digital materials, which align with current trends in educational technology. The analysis of the results suggests that incorporating digital resources into PJOK instruction can significantly improve student engagement and address practical needs. The findings highlight the importance of adapting teaching materials to fit students’ preferences and technological advancements. By developing e-modules that cater to these preferences, educators can enhance the learning experience and better support students in mastering both the theoretical and practical aspects of PJOK. This research underscores the need for a balanced approach in educational resource development, integrating both digital and traditional materials to create a comprehensive learning environment.